Optimalisasi Media Sosial dan Pengembangan Kreatifitas Anak Didik Sekolah Harapan di Desa Sinduadi, Kab. Sleman, Yogyakarta - Alvian Alrasid Ajibulloh; P, Angga Intueri Mahendra (TAAWUN, 2022)
Harapan School was built to realize children’s independence in learning. The activities include providing learning assistance and recitation guidance for children in Sinduadi Village, Sleman, Yogyakarta. The hope of realizing a better future for children is realized through education. Harapan School currently has one learning location, namely Sinduadi Village. The mentoring and guidance for children in Sinduadi Village with full glory and sincerity carried out by Harapan School succeeded in moving the hearts of this Activity Team and wanting to introduce Harapan School to a broader scope. This Activity Team plans to carry out a promotional program in the form of a company profile which will later be promoted through the social media owned by Sekolah Harapan (such as Instagram and Tiktok) and developed. This activity team hopes this will make Harapan School more widely known by the broader community by taking advantage of the current advances in social media technology and more volunteers who come to help Harapan School